2020
DOI: 10.1101/2020.04.14.041863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocyte- and neuron-derived extracellular vesicles from Alzheimer’s disease patients effect complement-mediated neurotoxicity

Abstract: We have previously shown that blood astrocytic-origin extracellular vesicles (AEVs) from Alzheimer's disease (AD) patients contain high complement levels. To test the hypothesis that circulating EVs from AD patients can induce complement-mediated neurodegeneration, we assessed the neurotoxicity of immunocaptured AEVs (with anti-GLAST antibody), neuronal-origin NEVs (with anti-L1CAM antibody), and multicellularorigin (with anti-CD81 antibody) EVs from the plasma of AD, frontotemporal lobar degeneration (FTLD) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…The study that measured betaIII-tubulin immunoselected using an antibody raised to a luminal L1CAM epitope (Zou et al, 2020), which may complicate interpretation. Another study detected glial fibrillary acidic protein (GFAP) in putative L1CAM+ material (Nogueras-Ortiz et al, 2020), an unexpected result. Finally, a proteomics study of L1CAM capture identified two proteins that were significantly enriched in brain, but also found significant enrichment of components of common contaminants of EV preparations, including circulating IgG complexes, HDL, very low-density lipoproteins (VLDL) and chylomicrons (Winston et al, 2016).…”
Section: Negative/depleted Non-ev Markersmentioning
confidence: 93%
See 1 more Smart Citation
“…The study that measured betaIII-tubulin immunoselected using an antibody raised to a luminal L1CAM epitope (Zou et al, 2020), which may complicate interpretation. Another study detected glial fibrillary acidic protein (GFAP) in putative L1CAM+ material (Nogueras-Ortiz et al, 2020), an unexpected result. Finally, a proteomics study of L1CAM capture identified two proteins that were significantly enriched in brain, but also found significant enrichment of components of common contaminants of EV preparations, including circulating IgG complexes, HDL, very low-density lipoproteins (VLDL) and chylomicrons (Winston et al, 2016).…”
Section: Negative/depleted Non-ev Markersmentioning
confidence: 93%
“…Five studies that did not specifically combine L1CAM and EVs were also removed. A total of 51 articles thus satisfied all criteria (see Figure 1 and list of papers in Table S1) (Anastasi et al, 2021;Athauda et al, 2019;Bhargava et al, Goetzl et al, 2019;Goetzl et al, 2015;Goetzl, Peltz, Mustapic, Kapogiannis, & Yaffe, 2020;Gomes et al, 2015;Gu et al, 2020;Gutwein et al, 2003;Gutwein et al, 2005;Herrero et al, 2019;Jiang et al, 2020;Jiang et al, 2021;Keller et al, 2009;Kodidela et al, 2020;Kumar et al, 2021;Mansur et al, 2021;Mullins, Mustapic, Goetzl, & Kapogiannis, 2017;Nasca et al, 2021;Nogueras-Ortiz et al, 2020;Norman et al, 2021;Pace, Dutt, & Galileo, 2019;Patterson, Deep, & Brinkley, 2018;Peltz et al, 2020;Pulliam, Liston, Sun, & Narvid, 2020;Rani et al, 2019;Shi et al, 2016;Shi et al, 2014;Si et al, 2019;Stoeck et al, 2006;Suire et al, 2017;Sun, Dalvi, Abadjian, Tang, & Pulliam, 2017;Sun, Fernandes, & Pulliam, 2019;Trnka, Ivanova, Hiatt, & Matsell, 2012;Walker et al, 2021;Webber et al, 2014;Winston et al, 2019;Winston et al, 2016;…”
Section:  Literature Search and Selectionmentioning
confidence: 96%
“…High complement levels can also be found in astrocytic EVs and neuronal EVs (Goetzl et al, 2018). These inflammatory EVs cause cellular membrane disruption and neurite density reduction in rat cortical neurons by activating membrane attack complex (MAC) formation (Nogueras-Ortiz et al, 2020). Age-associated chronic inflammatory states are similarly evident during PD progression.…”
Section:  Neurodegenerationmentioning
confidence: 99%
“…For instance, it was shown that astrocyte-derived EVs from plasma of AD patients and patients with mild cognitive impairment (MCI) who are converting to dementia contain significantly higher complement levels compared to controls and stable MCI patients [ 40 , 41 ]. Furthermore, astrocyte-derived EVs separated from plasma of AD patients exert neurotoxicity in neuronal cultures due to their high levels of several complement proteins [ 42 ]. The complement system is a rapid and efficient immune surveillance system, but when imbalanced it contributes to a variety of disorders including AD [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%